Effect of pulsed pressure-assisted brining on lipid oxidation and volatiles development in pork bacon during salting and drying-ripening. Issue 2 (December 2015) - Jin, Guofeng; He, Lichao; Li, Chengliang; Zhao, Yuhua; Chen, Cheng; Zhang, Yuehan; Zhang, Jianhao; Ma, Meihu
Abstract In this study, the pulsed pressure-assisted brining technology was used for bacon brining, and its effect on the moisture and lipid oxidation changes during drying-ripening period as well as the flavor composition of final products was investigated by determining the moisture content, acid value, peroxide value, TBARS value and volatile flavor compounds in meat samples during brining and drying-ripening. The results indicated that pulsed pressure-assisted brining could effectively increase the muscle water-holding capacity and decreased the sodium nitrite residues in final cured bacons. After drying-ripening (48 h) the moisture and sodium nitrite content in pulsed pressure-assisted brined samples and control samples were 32.84%, 14.56 mg/kg dry basis and 29.81%, 18.59 mg/kg dry basis, respectively. In addition, the lipid oxidation was promoted by pulsed pressure treatment (P < 0.05), and thus forming more lipid oxidation originated flavor compounds (esters, alcohols and aldehydes) in the pulsed pressure-assisted brined bacons than in control bacons. These suggested that pulsed pressure-assisted brining could effectively improve the sensory quality of cured bacon.